Cluster and principal component analysis of maize inbred lines in low moisture stress areas in Ethiopia - Talefe Wendwessen (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
This study used to cluster and principal component analysis to assess the agronomic and physiological variability of 40 maize inbred lines under low moisture stress conditions in Ethiopia. The study was conducted at Melkassa locations during the 2017 main season. The analysis of variance showed the mean square due to genotype was highly significant (p < 0.01) for all traits which indicates the existence of sufficient genetic variability and potential for selection and improvement on the characters. Cluster analysis revealed four distinct groups of inbred lines, The members of clusters 1 and 4 may be combined in future breeding programs to obtain genotypes/hybrids that can perform well under drought stress conditions. The inter-cluster D2 values varied from 48.65 to 4407 indicating the high range of diversity present among the genotypes. while principal component analysis showed the first six PCs having Eigen value >1 explaining principal components that accounted for 77.7% of the total variation among the inbred lines. The first three principal components PC1, PC2, and PC3 with values of 25.25%, 18.03, and 11.7% respectively more contributed. Grain yield, plant height, ear height, and the number of leaves per plant were the most important traits influencing the variability among the inbred lines.